Two-Pulse Phase Modulation Based Decoupling Schemes for Removing Heteronuclear Spin Interactions in the NMR Spectroscopy of Isotropic Systems: An Analysis Using Experiments and Numerical Simulations. (14th May 2014) - Augustine, Cyril
Abstract : Heteronuclear spin interactions in solids and anisotropic liquids can be removed by phase modulated decoupling sequences with frequency sweep, such as SW f -TPPM and its variants. The performance of these sequences in isotropic spin systems with regard to the experimental parameters, phase angle, and decoupler offset is presented here. A comparison is made with other commonly used heteronuclear decoupling schemes in liquids, namely, WALTZ-16, GARP, and MLEV. Also, the trajectories of nuclear magnetization vector of abundant nuclei in a simple spin system during TPPM and SW f -TPPM decoupling sequences are traced out using computer simulations.